DEVELOPMENT OF AUDIO VISUAL LEARNING MEDIA AS A STRENGTHENING OF DIGITAL LITERACY - Tony Mirwanto; Sri Kuncoro Bawono (Jurnal Abdimas Imigrasi, 2022)
The development of Information and Communication Technology (ICT) is rapid and impacts the learning process in the madrasah. The use of learning resource media is not only limited to printed resources, but also digital resources. This kind of phenomenon demands an increase in the capacity of madrasah teachers to produce digital-based media, especially in recent years, where online distance learning has been booming. The development of joyful and technology-based press is necessary, as well as an implementation of strengthening digital literacy. Madrasah teacher training and assistance need to be carried out to help upgrade their ability to create digital media (audio-visual) that can be applied in the learning process. This Community Service (CS) aims to increase the insight and skills of teachers at SMA Pelita Utama Kepulauan Riau is carried out in the form of digital literacy seminar activities and training in making audio-visual teaching media. The significance and contribution of digital literacy is instilled in madrasah teachers up to the process of making audio-visual media. The results of CS can be seen in the ability of madrasah teachers to create ICT- based media; indications of skills are seen in utilizing several applications, including; canva, toon app, remove background, and recorder. Each of these applications has its function as a medium for formulating teaching materials into audio-visual media.